Impact of a Multi-Strain Probiotic on Healthcare-Associated Bloodstream Infection Incidence and Severity in Preterm Neonates - Marwyn Sowden; Mirjam Maria van Weissenbruch; Andre Nyandwe Hamama Bulabula; Angela Dramowski; Carl Lombard; Evette van Niekerk (Galenos Yayinevi, 2022)
Aim:Hospital acquired bloodstream infection (HA-BSI) is a major contributor to morbidity and mortality in preterm, very low birthweight infants, especially in low-to-middle- income countries.Materials and Methods:We conducted a double-blind, placebo-controlled, randomized clinical trial to investigate the effect of a multi-strain probiotic formulation (LabinicTM) on the incidence and severity of HA-BSI in preterm neonates.Results:Two hundred neonates (100 per arm) were included in this trial. Fifteen neonates developed HA-BSI events (2 in the probiotic arm and 13 in the placebo arm). The median day of life at HA-BSI onset for the probiotic group was 10.5±3.5, and for the placebo group, it was 11.2±6.4. The incidence of HA-BSI in neonates receiving the probiotic was significantly lower compared to those receiving the placebo [0.93 versus 5.99 HA-BSI events/1,000 neonate-days; incidence rate ratio (IRR) of 0.156 [95% confidence interval (CI): 0.017 to 0.691], p=0.0046]. Calculating the incidence rate of the combined outcome (sepsis/death) was also lower in the probiotic group versus the placebo group [2.34 versus 6.45 events/1,000 neonate days; IRR 0.33 (95% CI: 0.11 to 0.97), p=0.043].Conclusion:The use of a multi-strain probiotic significantly reduced HA-BSI incidence in this cohort of preterm neonates.